Boy's and girl's learnt differently: language learning strategies and academic achievement in single sex and co-ed schooling - Ahmad, Nor Aniza (IATED Academy, 2015)
This study was conducted to identify the language learning strategies based on academic achievement of boys and girls. The instruments of language learning strategies were distributed to 400 students, aged 15 years old, of single gender schools and co-educational schools. The data were analysed using descriptive and inferential statistics. Preliminary review of secondary data found that girls’ academic achievement is consistently higher than boys' academic achievement in Malay and English language subjects. Furthermore, the language subject achievement of girls in co-educational schools is better than girls’ achievement in single gender school. Multiple discriminant analysis also shows significant differences for all constructs of Malay language learning strategies; learning strategies inside the classroom, learning strategies outside the classroom and learning strategies prior to examination. This study provides an understanding of the trends and gaps in language subject achievement by gender and type of schools. This study also suggests the needs for creativity and innovation in pedagogical practices especially in language learning strategies.